Exploring Kali Bicarbonicum –A Less Known Remedy (Advancements in Homeopathic Research, 2022)
Introduction: Kali bicarbonicum is a less known remedy. Its symptomatology is not present in any popular materia medica(s). Objective: This work is aimed to collect the data related to this remedy and present in a materia medica format. Methodology: Database search was done in old homoeopathic literature through google scholar, archive.org, RADAR homoeopathic software and libraries of different institutions. Further, symptomatology of closely related drugs were also taken into consideration. A combined materia medica has been compiled with the available information. Results and discussions: Kali bicarbonicum has a role mainly in brain, heart and skeletal muscle. It has characteristic symptoms including soft pulse, coldness, general depression, and the characteristic stitches felt in different parts, tenacious and slimy discharges,sharp and cutting pains better by motion.
Keywords: Kali bicarbonicum; symptomatology; RADAR; homoeopathic literature